Genetically Engineered Hepatitis C Virus-like Particles (HCV-LPs) Tagged with SP94 Peptide to Acquire Selectivity to Liver Cancer Cells via Grp78 - Dina Mofed; Mohamed A. Wahba; Tamer Z. Salem (Current Issues in Molecular Biology, 2022)
Targeted cancer therapy is a challenging area that includes multiple chemical and biological vehicles. Virus-like particles (VLPs) combine safety and efficacy in their roles as potential vaccines and drug delivery vehicles. In this study, we propose a novel drug delivery system based on HCV-LPs engineered with SP94 and RGD peptides mediated by a specific molecular chaperone (Grp78) associated with cancer drug resistance. The PCR primers were designed for engineering two constructs, SP94-EGFP-CORE-HIS and RGD-EGFP-CORE-HIS, by sequential PCR reactions. The two fragments were cloned into pFastBac Dual under the polyhedrin promoter and then used to produce two recombinant baculoviruses (AcSP94 and AcRGD). The VLP’s expression was optimized by recombinant virus infection with different MOIs, ranging from 1 to 20 MOI. Recombinant VLP2 were purified by Ni-NTA and their sizes and shapes were confirmed with TEM. They were incubated with different types of cells prior to examination using the fluorescence microscope to test the binding specificity. The effect of the overexpression of the Grp78 on the binding affinity of the engineered VLPs was tested in HepG2 and HeLa cells. The protocol optimization revealed that MOI 10 produced the highest fluorescence intensities after 72 h for the two recombinant proteins (SP94-core and RGD-core). Moreover, the binding assay tested on different types of mammalian cells (HeLa, HEK-293T, and HepG2 cells) showed green fluorescence on the periphery of all tested cell lines when using the RGD-core protein; while, the SP94-core protein showed green fluorescence only with the liver cancer cells, HepG2 and HuH7. Overexpression of Grp78 in HepG2 and HeLa cells enhanced the binding efficiency of the engineered VLPs. We confirmed that the SP94 peptide can be specifically used to target liver cancer cells, while the RGD peptide is sufficiently functional for most types of cancer cells. The overexpression of the Grp78 improved the binding capacity of both SP94 and RGD peptides. It is worth noting that the SP94 peptide can function properly as a recombinant peptide, and not only as a chemically conjugated peptide, as heretofore commonly used.